Formação de professores para a escola de educação básica: artes em sociais aprendizagens ou um voo coletivo - Abreu, Yure Pereira de (2024)
Initial education for arts teachers to work in elementary schools is an important scrutiny theme in Brazilian educational context; it requires carrying out research in order to comprehend better how that occurs, what are the implications from it and how it can be improved. Assuming that the school is a socially essential place for human development, and absolutely necessary to teachers’ education, we’ll introduce this research with the purpose of reflecting on the initial education of arts teachers, based on the principles of Shared Musical Apprenticeship, and their insertion in school ambience. More specifically, we aim to think about overcoming the banking model of education, and also think about relations and possibilities in teaching and learning that can provide wide cultural, creative, and aesthetic education, having the human beings as focus of the work. We discuss the importance of the teachers’ job and the insertion of college students since the beginning of their course. We’ll search pedagogical and didactic alternatives destined to arts teachers’ education so that college students can invent themselves as education professionals. We’ll verify the possibility of expanding teacher’s education pedagogy of Shared Musical Apprenticeship over the scope of music. For this purpose, we’ll use a dialectical approach with bibliographic character in a qualitative nature, to fulfil intentions and answer proposed questions. We intend to think about the scholar institution and how schools are privileged places for teachers’ education, more specifically arts teachers. We’ll reflect about arts in elementary education, about creativity as a human action and its role in formative processes, and also reflect about pre- and post-figurative teaching experiences. We’ll resort to renowned authors and intend to present laws written throughout the history of our country, about teachers’ education and arts teaching in elementary education. We aim to comprehend and articulate dialectically the thoughts of several authors about school; since those who understand the school as an ideological machine of the bourgeois state, having the purpose of maintaining class relations as they are; to those who use oppressive educational methods; and also researchers that perceive the school as a communist invention, breaking through privileges and providing opportunities for everyone to have free time to study. With the purpose of understanding what human education is, we come across the German modern tradition of education - Bildung - and we also study Shared Musical Apprenticeship. We come to the conclusion that it’s possible to overcome the school as it is nowadays - oppressive, neoliberal and capitalist - in order to implement a more human and solidary teaching action; and we comprehend that the participation of college students in school since the first period of their higher education is fundamental. We present, by consequence, a concrete alternative: Arts in Social Apprenticeship, a path to arts teachers education and to the arts approach at school.